PERSPECTIVES OF DIATOM TECHNIQUE FOR THE MONITORING OF HYDROMETEOROLOGICAL INFLUENCE ON SEDIMENTARY PROCESSES - Tymchenko, Yu.; Nasedkin, Y. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
New monitoring data on siliceous microalgae assemblages in the Black Sea Experimental Polygon near the South Crimea shore are examined. Seasonal changes on diatom number and abundance are analyzed. Perspective applications of diatom technique for the monitoring of abiotic influence on sedimentary processes are determined.